A bioinformatics approach to investigate serum and hematopoietic cell-specific therapeutic microRNAs targeting the 3' UTRs of all four Dengue virus serotypes. Issue 8 (5th October 2021) - Baig, Mirza Sarwar; Krishnan, Anuja
ABSTRACT: Hyperendemic circulation of all four Dengue virus (DENV) serotypes is a severe global public health problem, so any vaccine or therapeutics should be able to target all four of them. Cells of hemopoietic origin are believed to be primary sites of DENV replication. This study aimed to identify potential host miRNAs that target 3' UTR of all four DENV serotypes, thereby directly regulating viral gene expression or indirectly modulating the host system at different virus infection steps. We used four prediction algorithms viz. miRanda, RNA22, RNAhybrid and StarMir for predicting miRNA, targeting 3'UTR of all four DENV serotypes. Statistically, the most significant miRNA targets were screened based on their Log10 P -value (> 0.0001) of Gene Ontology (GO) term and Kyoto Encyclopaedia of Gene and Genome (KEGG) pathway enrichment analysis. The intersection test of at least three prediction tools identified a total of 30 miRNAs, which could bind to 3'UTR of all four DENV serotypes. Of the 30, eight miRNAs were of hematopoietic cell origin. GO term enrichment and KEGG analysis showed four hemopoietic origin miRNAs target genes of the biological processes mainly involved in the innate immune response, mRNA 3'-end processing, antigen processing and presentation and nuclear-transcribed mRNA catabolic process. Abstract : MicroRNAs targeting all four dengue serotypes identified using a bioinformatics approach.